Polymorphisms of the IgH enhancer HS1.2 and risk of systemic lupus erythematosus. Issue 8 (31st January 2012) - Frezza, Domenico; Tolusso, Barbara; Giambra, Vincenzo; Gremese, Elisa; Marchini, Maurizio; Nowik, Marcin; Serone, Eliseo; D'Addabbo, Pietro; Mattioli, Claudia; Canestri, Silvia; Petricca, Luca; D'Antona, Graziella; et al.
Abstract : Objective: To determine whether the allelic frequency variation of the HS1.2 enhancer of the immunoglobulin heavy chain (IgH) 3′ regulatory region (3′RR-1) locus represents a risk factor for systemic lupus erythematosus (SLE) and to identify a possible functional difference in the two most frequent alleles (*1 and *2) in binding nuclear factor- κB (NF-κB) and Sp1. Methods: The frequency of the enhancer HS1.2 alleles was determined in two cohorts of patients with SLE (n=293) and in 1185 controls. Electrophoretic mobility shift assays (EMSA) were carried out with B cell nuclear extracts with different probes of HS1.2 alleles *1 and *2 to map the consensus binding sites of the nuclear factors. A confirmatory cohort of 121 patients with SLE was also included. Results: The frequency of allele *2 of the HS1.2 enhancer was significantly increased in patients with SLE compared with controls (OR 1.60, 95% CI 1.33 to 1.92, p<0.001). EMSA experiments showed the presence of the Sp1 binding site in both alleles whereas only allele *2 carried the consensus for the NF-κB factor. The presence versus absence of allele *2 in patients with SLE correlated with a higher concentration of IgM levels and with the expression of B cell activating factor receptor (BAFF-R). Conclusions: The increased frequency of allele *2 in patients with SLE identifies a new genetic risk factor for SLE. A possible biological effect of the polymorphism could be the difference observed in the localisation of an NF-κB binding site which is specific for allele *2 and absent in allele *1. These observations suggest a functional effect of the HS1.2 enhancer in this disease.